Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.5194/amt-15-4001-2022
|View full text |Cite
|
Sign up to set email alerts
|

Testing the efficacy of atmospheric boundary layer height detection algorithms using uncrewed aircraft system data from MOSAiC

Abstract: Abstract. During the Multidisciplinary drifting Observatory for the Study of Arctic Climate (MOSAiC) expedition, meteorological conditions over the lowest 1 km of the atmosphere were sampled with the DataHawk2 (DH2) fixed-wing uncrewed aircraft system (UAS). These in situ observations of the central Arctic atmosphere are some of the most extensive to date and provide unique insight into the atmospheric boundary layer (ABL) structure. The ABL is an important component of the Arctic climate, as it can be closely… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…As the base of a TI is often located at or near the top of the ABL, and we also saw increasing ABL height with decreased stability, this makes sense. However, the large jump in TI altitude 585 for all regimes with weak stability aloft shows that TI altitude is not always the best method for determining ABL height, which agrees with Jozef et al (2022). This is further supported by the difference between TI base height and ABL height (Fig.…”
Section: Temperature Inversionsmentioning
confidence: 65%
See 2 more Smart Citations
“…As the base of a TI is often located at or near the top of the ABL, and we also saw increasing ABL height with decreased stability, this makes sense. However, the large jump in TI altitude 585 for all regimes with weak stability aloft shows that TI altitude is not always the best method for determining ABL height, which agrees with Jozef et al (2022). This is further supported by the difference between TI base height and ABL height (Fig.…”
Section: Temperature Inversionsmentioning
confidence: 65%
“…ABL height from each radiosonde profile was determined using a bulk Richardson number (Rib) based approach in which the top of the ABL was identified as the first altitude in which Rib exceeds a critical value of 0.5 and remains 185 above the critical value for at least 20 consecutive meters (Jozef et al, 2022). The methodology for calculating the Rib profile used to identify ABL height follows that described in Jozef et al (2022) and Jozef et al (submitted). Once ABL height was identified, we determined the vertical gradient in virtual potential temperature (dθv/dz) and horizontal wind speed (dV/dz) between 35 m and the top of the ABL for each radiosonde.…”
Section: Deriving Quantities From Observational Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, turbulence can still be present beyond Ri c (Sukoriansky et al, 2006), shown by a large number of meteorological and oceanographic observations (e.g., Kondo et al, 1978;Yagüe et al, 2001;Mack and Schoeberlein, 2004). Further, Jozef et al (2022a) found that a value of Ri g =0.5 to 0.75 on the vertical profile can be used to determine the ABL height based on DH2 MOSAiC data.…”
Section: Richardson Numbermentioning
confidence: 96%
“…Indeed, the formation of HCl can serve as a sink for chlorine compounds in the troposphere, where HCl is taken up by aerosols and converted into Cl − , followed by an atmospheric deposition process 14,53 ; although, in the presence of NO x and reactive halogens (i.e., HOI and The reactions are based on the literatures 2,[12][13][14]64 . The mean boundary layer height was reported to vary between 100 and 200 m during the MOSAiC campaign 74,78 .…”
Section: Atmospheric Fate Of Hclo 3 and Hclomentioning
confidence: 99%